The near consumer insight on liver proteomics of Malaysian broiler in comparison with indigenous chicken - Abu Hassan, Muhamad Shafiq; Saidin, Muhammad Syazwan; Hamdan, Nurul Ashima; Abd Hamid, Shafida; Muhamad Bunnori, Noraslinda (World Research Library, 2018)
In this study, the differences in protein expression from chicken liver between commercial broilers (CB) and indigenous chicken (IC) have been analysed by using two-dimensional gel electrophoresis (2D-PAGE). The study was conducted adjacent to consumer experience in order to find out the differences of the protein profile in liver tissues between the two popular types of chickens that have been offered to the Malaysians consumer for over 50 years. In 2D-PAGE, six spots were successfully identified deferentially expressed in term of intensity. Those proteins are phosphoenol pyruvate carboxykinase (PEPCK) (2 spots), delta-1-pyrolline-5-carboxylate (P5CDH), soluble epoxide hydrolase (sEH), heat shock protein 90 (HSP90) and γ-actin. PEPCK and P5CDH enzymes were expressed higher in CB compared to IC, suggesting the utilization of alternative metabolic pathways for broilers’ energy metabolism. The sEH expression was found higher in CB compared to IC probably due to the process of xenobiotic metabolic activity to eliminate harmful epoxide inside the CB’s liver. HSP90 was found less in CB compared to IC, which may indicate the lack of regulation of heat stress response in CB. The higher expression of actin in IC liver suggested a good form of structure integrity in IC liver compared to CB, which may happen due to the age differences.Most of the differentially expressed proteins are involved in energy metabolism, stress regulation, and cellular structure.These differences could arise from many variables involved which may include breeds, age, feed regimen, drug treatment and rearing environment.